Avtomatska vozila in mobilni roboti v intralogistiki - Lerher, Tone (University of Maribor Press, 2022)
Automated Vehicles and Mobile Robots in Intralogistics. The textbook deals with the automation and robotisation of internal transport in intralogistics, where automated guided vehicles AGV and autonomous mobile robots AMR are discussed. In addition to the technicaltechnological characteristics of AGV and AMR, individual implementations of AGV and AMR that are more widely used in l,ogistics are presented. The textbook deals specifically with automatic vehicles for working in automated storage systems and autonomous mobile robots for use in future warehouses. Basic analytical and numerical models for determining the throughput performance of AGVs and AMRs in warehouse systems are presented. In addition to AGV and AMR solutions in warehouses that are already established in practise, new conceptual designs of automated and robotic warehouse systems with AGV and AMR are presented that are currently still in the·design and further development phase.